Gen Z and Web Reputation Management in Social Media. What Are the Implications for Digital Capital? - Marino, Rosanna; Matteo, Miriam (Italian Sociological Review, 2024)
Starting from the debate on Internet risks and opportunities for young people, the article focuses on the topic of web reputation in social media, and analyses GenZers’ web reputation management strategies on social network sites. The study, based on empirical research conducted in the Campania region (South Italy) during the COVID-19 pandemic, describes the most relevant practices adopted by young people to cope with risky online experiences with the aim of minimizing the harm received, and the role of key agencies in mediating risks and supporting coping strategies. This work is intended to be useful for reflecting on the possibility of viewing young people’s web reputation management strategies in relation to the concept of digital capital, drawing new considerations from the logic that rules the opportunities and risks dialectic arising from the use of social media.